Cory Corazon Aquino and the Philippines - Siegel, Beatrice (Dutton, 1988)
A biography of the political newcomer who ran for the office of president of the Philippines following her husband's assassination and defeated Ferdinand Marcos in the 1986 election. Includes an interview with President Aquino.